2018
DOI: 10.1021/acs.jced.7b00534
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Solubilities in Decanoic Acid-Based Hydrophobic Deep Eutectic Solvents

Abstract: The solubility of CO2 in hydrophobic deep eutectic solvents (DESs) has been measured for the first time. Six different hydrophobic DESs are studied in the temperature range from 298 to 323 K and at CO2 pressures up to 2 MPa. The results are evaluated by comparing the solubility data with existing hydrophilic DESs and currently applied physical solvents and fluorinated ionic liquids. The DESs are prepared by mixing decanoic acid with a quaternary ammonium salt with different halide anions and alkyl chain length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 24 publications
(37 reference statements)
2
98
1
Order By: Relevance
“…used the perturbed‐chain statistical associating fluid theory (PC‐SAFT) equation of state for modelling the CO 2 solubilities in several hydrophobic (D)ESs. Afterwards, Zubeir et al . measured the solubility of CO 2 in hydrophobic (D)ESs in which decanoic acid was combined with five different hydrophilic and hydrophobic quaternary ammonium salts, in the temperature range from 25 to 50 °C and at CO 2 pressures up to 2 MPa.…”
Section: Hydrophobic (Deep) Eutectic Solventsmentioning
confidence: 99%
“…used the perturbed‐chain statistical associating fluid theory (PC‐SAFT) equation of state for modelling the CO 2 solubilities in several hydrophobic (D)ESs. Afterwards, Zubeir et al . measured the solubility of CO 2 in hydrophobic (D)ESs in which decanoic acid was combined with five different hydrophilic and hydrophobic quaternary ammonium salts, in the temperature range from 25 to 50 °C and at CO 2 pressures up to 2 MPa.…”
Section: Hydrophobic (Deep) Eutectic Solventsmentioning
confidence: 99%
“…In order to be able to evaluate whether the use of DESs for CO 2 absorption can be economically feasible, it is necessary to ascertain whether desired properties are realistic for a DES. Scientific papers have been reviewed in the pursuit of a DES with high CO 2 solubility, including CO 2 absorption by choline chloride based DESs (Isaifan and Amhamed, 2018), by decanoic acid based hydrophobic DESs (Zubeir et al, 2018) and by other reported DESs (Sarmad et al, 2017). In the work of Sarmad et al (2016) several DESs have been screened in terms of their CO 2 solubility and viscosity.…”
Section: Literature Review Of Deep Eutectic Solvents and Economic Anamentioning
confidence: 99%
“…DESs are a mixture consisting mainly of two or three non-toxic and biodegradable compounds that are capable of forming eutectic liquids, based on the specific interaction between hydrogen bond donor (HBD) and hydrogen bond acceptor (HBA) [27,28]. Until now, DESs have been widely used for desulfurization of fuels [9], biomass pre-treatment [29], water and air purification [30,31], in catalysis [32], and analytical chemistry [27,33,34]. Till now, no studies have been in the literature published regarding the use of DESs as absorbents to remove volatile organosulfur compounds from the biogas stream.…”
Section: Vscsmentioning
confidence: 99%